Synthesis and Reactivity of Allenylporphyrins - SENGE, MATHIAS; PLUNKETT, SHANE (My University, 2013)
Several different methods have been utilized for the effective synthesis of a new class of porphyrins that contains the synthetically intriguing propadienyl (or allenyl) functional group. Of these approaches, successive Horner?Wadsworth?Emmons couplings proved impossible, but Pd-catalyzed cross-coupling reactions enabled quick and easy synthetic access to allenylporphyrins. The conditions for the Suzuki?Miyaura cross-coupling reaction of bromoporphyrins with allenylboronic acid pinacol ester were optimized. This reaction represents the first successful use of this boronic acid in a Suzuki-type coupling. Although this routine was successful for the syntheses of porphyrins that contain aromatic substituents, a more robust method was also developed that involves a Sonogashira coupling of a bromoporphyrin with N,N-diisopropylprop-2-yn-1-amine followed by a Pd-catalyzed rearrangement to give allenylporphyrins in high yields. For both routes, the applicable metalation states of the porphyrin core were investigated with mixed results. The utility of the addition of the allenyl functional group was then probed with both directly linked allenylporphyrins and those containing a phenyl ?spacer?.
PUBLISHED
Keywords: porphyrins